Literature Review: Accidents in the Material and Construction Industry - Wahab, Nurhana Abd; Mahmood, Nik Hasnaa Nik; Minghat, Asnul Dahar (ASEAN Journal for Science and Engineering in Materials, 2023)
The material and construction industry plays a big role to contribute to the country’s development and indirectly contributes to improving the quality of life for locals. Here, the focus of this paper is on the literature review on accidents in the material and construction industry, problems causing the accident, the safety training impact and influences, issues related to the method of training, the model of learning and training for Occupational Safety and Health, and the effectiveness of training method. This paper can become the references for practitioners and industrial sectors as well as stakeholders and government.